The ability to manage uncertainty for solid radioactive waste characterization in the UK nuclear industry - Peter J. Hiller; Caroline K. Pyke; Chris P. Lennon; Olivia C.G. Tuck; Caitlin A. Painter (Nuclear Engineering and Technology)
The disposal of radioactive waste within the UK is managed through a comprehensive regulatory framework. This framework requires radioactive waste to be sufficiently well characterized to ensure its disposal is compliant with the regulations and the acceptance criteria for any receiving facility. This is the responsibility of both the waste consignor and the receiving facility.Characterization of solid radioactive waste is extremely challenging. This is due to the wastes exhibiting a high degree of heterogeneity which leads to significant uncertainty. Understanding the total uncertainty requires combining the uncertainties associated with numerous stages of the characterization process.Experience suggests that whilst uncertainties are included in waste characterization, approaches are variable in quality. This makes it challenging to present an appropriate level of confidence in the waste characterization and the subsequent decisions made to stakeholders.This paper introduces the concept and principles of uncertainty and uncertainty management in waste characterization, summarizing challenges, and gaps in the current approach. It recommends a solution is sought to address shortfalls in the understanding of uncertainty; identify sources of uncertainty across the whole characterization lifecycle; and agree how specialists might combine these uncertainties and communicate them to stakeholders.